A incompatibilidade entre os direitos fundamentais : uma crítica libertária - Oliveira, Flávio Rodrigues de (2016)
Much discussion in political philosophy resolve around on key point: freedom versus equality. To a libertarian, such as the concept is understood in this work, formal or juridical equality (equality of all before the law), implies freedom. There`s no freedom if all aren`t juridically equal. Thus, ethny, sexual orientation, gender and economist status and other aspects that would bring a differentiation in the treatment between one and another, should be disregarded in the jurisdiction scope. More closely, any substantial equality, is despised by a libertarian, understanding that decisions taken in this field will only fair if, treat everyone, equal or unequal, as unique individuals, independent of any contingencies. Therefore, this defense of freedom, broached here, it`s seen in its negative aspect. Negative freedom should be understood as the sphere action where there is no coercions of other, physical. This point the view, this way freedom, is the only premise which should be required in the formulation of laws to society. Therefore, in the libertarian minarchist conception, friction between negative rights and positive historical rights does not justify the priority of the last, because the historical legitimacy is not enough evidence to its legality. In the historical ambit the positive rights were acquired by a bigger struggle of individual for a bigger representation in the State in society, however, we seek to show that these actions violate individual rights. Thereupon, a libertarian is always more cautions with the positive rights. For libertarians negative rights predate and are the reason of being any Constitution of right and should prevail also in the constitution of laws of Modern State. Thus, our work aims to analyze Brazil`s constitution considering the perspective of the construction of fundamental rights in generation of rights, showing the incompatibility between first rights (negative rights) and generation with subsequent rights (positivized rights).